Application of the electrical impedance method to steel/steel EHD point contacts - Maruyama, Taisuke; Kosugi, Daichi; Iwase, Shunsuke; Maeda, Masayuki; Nakano, Ken; Momozono, Satoshi (Frontiers in Mechanical Engineering, 2024)
The authors have previously developed the electrical impedance method which simultaneously measure the thickness and breakdown ratio of oil films in EHD (elastohydrodynamic) contacts. Furthermore, using a ball-on-disc-type apparatus, the authors have also confirmed that the accuracy of oil film measurement by the developed method is comparable to that of optical interferometry (i.e., glass-steel contacts). In this study, we discussed the experimental results obtained by applying the electrical impedance method to steel-steel contacts using a steel disc instead of a glass disc. It was found that under the mixed lubrication regime where wear occurs, the oil film thickness obtained by this method is calculated to be significantly thicker than the theoretical value. This can be attributed to the increase in the apparent dielectric constant of the lubricant due to wear particles in the lubricant.